Bridging the Divide: An Analysis of Community-Led Approaches in Sabah & Sarawak, Malaysia Rural Infrastructure Development (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Expanding rural infrastructure remains a key focus of Malaysia’s national agenda, though the merits of conventional, top-down approaches have come under criticism. This paper examines the pros and cons of using community-driven approaches to rural infrastructure development in Malaysia especially in Sarawak and Sabah. While using Empowerment Theory and Multi-Level Governance as theoretical perspectives, the literature and case study synthesis highlights the rhetoric vs. reality of participation of this situation. It argues that community-driven approaches to rural infrastructure development economically and socially empower the community, enhance the sustainability of the initiative through ownership, and promote effective problem solving by leveraging local knowledge. However, these advantages are largely absent in the community-driven approaches due to Malaysia’s centrally coordinated governance system, which comprises structural silos, a chronic lack of resources and capabilities, and token participation that remains community consultation. The Comparative Governance Framework (CGF) focuses on the deficits of the centralized governance system, particularly the Rural Transformation Programme (RTP), and the potential of hybrid governance as a governance model. It provides for centralised control with local governance autonomy, thereby offering a hybrid of central and local governance as a model. A genuine example happen in Sabah and Sarawak, showcases the mixed outcomes of top-down megaprojects such as the Pan Borneo Highway in contrast with bottom-up community initiatives in renewable energy, community water management, and ecotourism. The argue of participation and the reality of its implementation suggest the necessity of a shift from a protective to an empowering state. This paper understands bridging the gap between the rhetoric of participation and the reality of underground that requires a transition from a federalism to an enabling state. It proposes a set of policy and practice recommendations to support a hybrid model of governance that formally recognizes rural communities as active stakeholders and partners in their development, in order to achieve greater equity and sustainability.